IMPLEMENTASI ISLAMIC FINANCIAL PLANNING DALAM PERENCANAAN KEUANGAN PENGUSAHA MUSLIM ALUMNI GONTOR YOGYAKARTA - Purnomo, Agus; Maulida, Atika Zahra (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2017)
Wealth is something very important in human life, Islam has set wealth managementclearly both personal and public. Today the concept of Islamic Financial Planning is being developed as modern wealth management for Moslems which have been modified to adjust the demands of the times. The concept of Islamic Financial Planning is trying to accommodate the particula rneeds of the Muslim entrepreneurs. This study al soreviews and discusses about the implementation of Islamic Financial Planning among Muslim entrepreneurs. This study aims to capture and analyze the application of Islamic Financial Planningin business practices of Muslim entrepreneurs.This research is a field research. The object of this studyis entrepreneurs of Gontorâs Alumni (10 informants), who are assumed to have been very familiar with the Islamic property management. Data are collected through interviews, observation and documentation. It was then analyzed using a qualitative descriptive method. The result ofthis studyis that almost of the 10 informants have implemented both Islamic Financial Planning and Islamic wealth management. In the instruments of Investment, saving, and filantropy all of the ten informants have implemented. but the other instrument, like insurance, testament, and bequest, all informants havenât implemented yet. All informants have also implemented The guidance of Islamic Wealth Management, are: seeking for wealth (kasb), purchasing (infaq), and saving. Gontor also contributed in the business of informants, both in learning and networking.Â